A current view on the phenotypic antibiotic resistance of leading pathogens in wounded patients during the war in Ukraine - Kovalchuk, Valentyn; Riesbeck , Kristian; Nazarchuk, Oleksandr; Faustova, Mariia; Dmytriiev, Dmytro; Nazarchuk, Halyna; Chornopyshchuk, Roman; Levchenko, Bohdan (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The purpose of this study was to determine the effectiveness of antibacterial drugs through cluster analysis of antibiotic sensitivity data from clinical isolates of Acinetobacter and Pseudomonas spp., obtained from soft tissue wounds and burn injuries. Methods: The cohort included 76 clinical isolates of Gram-negative bacteria obtained from patients with combined injuries of soft tissues and burns. The final identification of the obtained isolates was carried using MALDI-ToF (Bruker). The sensitivity of clinical isolates to antibacterial drugs was determined using the standard Kirby-Bauer method. Extended antimicrobial susceptibility testing was performed to measure the minimal inhibitory concentrations of antibiotics against the studied. A hierarchical cluster analysis was performed using the Ward method. Results: The high level of resistance formation was observed among representatives of this Acinetobacter genus. We found the highest level of resistance in P. aeruginosa to ciprofloxacin. The lowest proportions of resistant Pseudomonas spp. were observed for meropenem and tobramycin. Cluster analysis of susceptibility data for P. aeruginosa isolates resulted in the division of antibiotics into two clusters with a significant dissimilarity distance. The isolated A. baumannii strains showed susceptible to a higher number of antibacterial drugs compared to P. aeruginosa. Conclusions: Clinical isolates of A. baumannii and P. aeruginosa obtained from patients with combined soft tissue injuries and burns in Ukraine in 2022 exhibit a high level of multidrug resistance. Cluster analysis results indicate that only tobramycin potentially retains efficacy against A. baumannii isolates. Clinical isolates of P. aeruginosa demonstrate susceptible to tobramycin and meropenem.